Formation of All Three C2H4O Isomers—Ethylene Oxide (c-C2H4O), Acetaldehyde (CH3CHO), and Vinyl Alcohol (CH2CHOH)—in Ethanol-containing Interstellar Analog Ices - Jia Wang; Chaojiang Zhang; Joshua H. Marks; Ralf I. Kaiser (The Astrophysical Journal)
Oxygen-containing complex organic molecules are key precursors to biorelevant compounds fundamental for the origins of life. However, the untangling of their interstellar formation mechanisms has just scratched the surface, especially for oxygen-containing cyclic molecules. Here, we present the first laboratory simulation experiments featuring the formation of all three C _2 H _4 O isomers—ethylene oxide ( c –C _2 H _4 O), acetaldehyde (CH _3 CHO), and vinyl alcohol (CH _2 CHOH)—in low-temperature model interstellar ices composed of carbon monoxide (CO) and ethanol (C _2 H _5 OH). Ice mixtures were exposed to galactic cosmic-ray proxies with an irradiation dose equivalent to a cold molecular cloud aged (7 ± 2) × 10 ^5 yr. These biorelevant species were detected in the gas phase through isomer-selective photoionization reflectron time-of-flight mass spectrometry during temperature-programmed desorption. Isotopic labeling experiments reveal that ethylene oxide is produced from ethanol alone, providing the first experimental evidence to support the hypothesis that ethanol serves as a precursor to the prototype epoxide in interstellar ices. These findings reveal feasible pathways for the formation of all three C _2 H _4 O isomers in ethanol-rich interstellar ices, offering valuable constraints on astrochemical models for their formation. Our results suggest that ethanol is a critical precursor to C _2 H _4 O isomers in interstellar environments, representing a critical step toward unraveling the formation mechanisms of oxygen-containing cyclic molecules, aldehydes, and their enol tautomers from alcohols in interstellar ices.